Development of Aluminium Oxide/polyamide 12 composite powders for direct laser sintering - Koh, Wee Kiat (2018)
The introduction of Additive Manufacturing (AM) technology is growing rapidly in this current era where researches and studies on its practicality have been carried out to make sure that this technology is being fully utilized in the progress of every countries. Over the decades, AM techniques have evolved and gained much attention. Direct metal laser sintering (DMLS) is one of the most fascinating AM techniques used to fabricate three-dimensional parts. In the current state of DMLS, metals such as titanium and aluminium are the materials used to print objects. However, there is a limitation on the materials used and therefore unable to meet the requirement to print a variety of objects. The primary goal of this project is to consider other alternative of materials used for DMLS process to produce laser sintered parts such as polyamide 12 and aluminium oxide composite powder and develop a method to prepare this composite powder. A dispersion technique will be developed to achieve a uniform dispersion of the composite powder for laser sintering process. Further, optimizing the ratio of the laser machine parameters will be done to achieve a good sintering result of the composite powder. Finally, it is important to study the effects on the surface morphology and properties of different ratio composite powder and its relationship with different parameters such as laser power, laser scan speed, and laser scan spacing of the laser machine.